The continuous path : Pueblo movement and the archaeology of becoming - Preucel, Robert W.; Duwe, Samuel (Amerind studies in anthropology., 2019)
"This book shows how archaeologists can incorporate Indigenous ways of knowing and being for a more collaborative approach"--Provided by publisher